1+2сos^2x=2sin2x
2+cos2x=2sinx
2sin2x-cos2x=2
ввожу замену
y=tgx
sin2x=2tgx/(1+tg^2x)=2y/(1+y^2)
cos2x=(1-tg^2x)/(1+tg^2x)=(1-y^2)/(1+y^2)
тогда уравнение примет вид
4y/(1+y^2)-(1-y^2)/(1+y^2)=2
4y-1+y^2=2+2y^2
y^2-4y+3=0
D=16-12=4
y1=3; y2=1
tgx=1; x=pi/4+pik
tgx=3; x=arctg3+pik
Так , если 32:8=4(1/8)
4•3=12(сл.)
рис а) А(1); B(4); C(6); D(-1); E(-4); F(-7); M(-0.5); K (2.5)
рис б) А(10); B(20); C(30); D(-10); E(5); F(-25); M(-32.5); K (-2.5)
Ответ:
Пошаговое объяснение:
2/3:(-2)=2/3*(-1/2)=-1/3
4:(-1/2)=4*(-2)=-8
(-5/6):(-5/12)=-5/6*(-12/5)=2
Я решала у меня получилось 481,87